Mitochondrial Ca2+ remodeling is a prime factor in oncogenic behavior - Alessandro eRimessi; Simone ePatergnani; Massimo eBonora; Mariusz R. Wieckowski; Paolo ePinton (Frontiers in Oncology, 2015)
Cancer is sustained by defects in the mechanisms underlying cell proliferation, mitochondrial metabolism and cell death. Mitochondrial Ca2+ ions are central to all these processes, serving as signaling molecules with specific spatial localization, magnitude and temporal characteristics. Mutations in mtDNA, aberrant expression and/or regulation of Ca2+-handling/transport proteins, and abnormal Ca2+-dependent relationships among the cytosol, endoplasmic reticulum and mitochondria can cause the deregulation of mitochondrial Ca2+-dependent pathways that are related to these processes, thus determining oncogenic behavior. In this review, we propose that mitochondrial Ca2+ remodeling plays a pivotal role in shaping the oncogenic signaling cascade, which is a required step for cancer formation and maintenance. We will describe recent studies that highlight the importance of mitochondria in inducing pivotal cancer hallmarks and discuss possible tools to manipulate mitochondrial Ca2+ to modulate cancer survival.